PERAN GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBINA ANAK DI ERA POSTMODERN - Yuel Sumarno; Hasiati Sinaga; Indri Yulianti (Edukasi : Jurnal Pendidikan Agama Kristen, 2021)
Child development in the postmodern era faces unique challenges, primarily due to the plurality and relativity dominating the understanding of truth. In this period, children are confronted with various perspectives that often contradict, leading to confusion about their identity and values. Christian parents and educators need to play a more significant role in instilling values based on biblical truth. In this context, the love of Christ becomes an unshakable centre in nurturing children. Through the unconditional love exemplified by Christ, children are taught to understand that they are valuable in the eyes of God, regardless of their background or abilities. Educators must use relevant and engaging methods, such as stories and parables, to convey moral and spiritual values. Moreover, positive interactions between parents and children through daily activities, such as playing and listening to stories, aid in children's emotional and social development. In formal education, teachers must integrate character and moral development into their curriculum, working alongside families to instil values of honesty, responsibility, and hard work. Through a holistic approach involving families, schools, and communities, children can grow in a supportive and loving environment, preparing them to face the challenges of the postmodern era with solid faith and good character.